Adolescent motor vehicle crash prevention through a trauma center–based intervention program. Issue 5 (November 2017) - Layba, Cathline; Griffin, Lance W.; Jupiter, Daniel; Mathers, Charles; Mileski, William
Abstract : ABSTRACT: Traumatic injuries account for millions of emergency room visits and hospital admissions annually. Motor vehicle crashes (MVCs) remain a leading cause of mortality between the ages of 1 and 44 years. With the popularity of smart devices, drivers are ever more distracted on the road. Programs that educate drivers on safe actions and to raise awareness of the perils of drunk and distracted driving exist, but there are few data that demonstrate a reduction in motor vehicle injury rates. We sought to determine if the implementation of such a program in our community would impact the rates of MVCs. Assessing the effectiveness of the Save A Life Tour, a risk reduction program, this intervention was instituted at a single area high school. The numbers of adolescent drivers aged 16 to 21 years involved in MVCs treated at the regional Level I trauma center were compared over two time intervals and between two adjoining counties. The time intervals consisted of preintervention and postintervention surveillance, each over a period of 3 years. Using our trauma registry, we compared the incidence of MVC between the two counties and between the two age groups. The data were also compared with the incidence among these populations nationally. In the preintervention period, the number of adolescent MVCs treated from the catchment area was 166, and the number in the postintervention period was 105. This represented a risk reduction of 37% ( p < 0.05). During the same intervals, the incidence in the nonintervention control catchment area increased by 12%. There was no significant change in the population aged 16 to 21 years over the time intervals in either area. These results suggest that ongoing educational intervention programs aimed at adolescent drunk and distracted driving can have an impact on these life-threatening behaviors and on the incidence of MVCs. LEVEL OF EVIDENCE: Therapy, level IV.